Intraoperative Evaluation of Ureteral Blood Flow Using Indocyanine Green Fluorescence imaging on Living-Donor Kidney Transplantation - Shiraishi, Yusuke (Hinyokika kiyo. Acta urologica Japonica, 2023)
Ureteral stenosis occurs in 2-10% after kidney transplantation. Most are caused by ischemia of the distal ureter and are difficult to manage. There is no standard method for evaluating ureteral blood flow during surgery, and it is left to the judgement of the operator. Indocyanine green (ICG) is used not only for a liver or cardiac function test but also for an assessment of tissue perfusion. We evaluated the intraoperative ureteral blood flow under a surgical light and by ICG fluorescence imaging in 10 living-donor kidney transplant patients between April 2021 and March 2022. No ureteral ischemia was detected under the surgical light, but ICG fluorescence imaging revealed/decreased blood flow in 4 of the 10 patients (40%). Further resection was performed in these 4 patients to increase the blood flow, and the median resection length was 1.0cm (0.3-2.0). The postoperative course was uneventful in all 10 patients, and no ureter-related complications were observed. ICG fluorescence imaging is a useful method for evaluating ureteral blood flow and is expected to help reduce complications caused by ureteral ischemia